2016
DOI: 10.1371/journal.pone.0152028
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Newborn Hearing Screening in Well-Baby Nursery and NICU: A Study Applied to Reduce Referral Rate in NICU

Abstract: ObjectivesTo determine whether newborn hearing screening in a well-baby nursery (WBN) and neonatal intensive care unit (NICU) nursery: 1) meet three targeted, screening, referral, and diagnostic follow-up rates; 2) compare the average age of diagnosis for infants admitted to the WIN and NICU; and 3) determine prevalence of hearing loss in neonatal population; and 4) try to find a practical newborn hearing screening time algorithm to reduce refer rate in NICUMaterials and MethodsIt examined 15,624 newborns in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 18 publications
1
16
2
Order By: Relevance
“…This study showed the average age of diagnosis to be 2.7 months, in agreement recent study by Li et al, 18 whose mean was similar to that of neonates coming from the neonatal ICU and the nursery.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study showed the average age of diagnosis to be 2.7 months, in agreement recent study by Li et al, 18 whose mean was similar to that of neonates coming from the neonatal ICU and the nursery.…”
Section: Discussionsupporting
confidence: 92%
“…The early diagnosis aims to reduce the consequences that hearing loss can bring, and the more reliable the result is, the more effective the hearing screening program becomes. 17 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been studies comparing NICU and healthy neonates in several countries and reporting associated risk factors. But few studies have been conducted in a large population with national database as this study, and a total of 524,371 newborns (WBG with 506,634 newborn and HRG who were admitted in NICU more than 5 days with 17,737 newborns) was enrolled [9,[13][14][15]. The purpose of this study was to compare NHS results between healthy newborns and infants who were admitted to the NICU for more than 5 days, to analyze the associated factors necessary to manage the national NHS program and to establish effective policy to support hearing impaired children.…”
Section: Discussionmentioning
confidence: 99%
“…From 2010 and on, the nationwide coupon-mediated NHS program collected data from enrolled newborns and identified details whether they were admitted to NICU for more than 5 days, which is one of the high-risk factors for HL according to JCIH 2007. The referral rate is mentioned to be much higher in NICU neonates (2.8-9.2%) [6][7][8][9], and the incidence of congenital HL is reported to be 2 to 4/100 in NICU neonates which is much higher than 1.8 to 3/1000 in well-babies [10][11][12]. Accordingly, it is necessary to track and manage NHS in NICU neonates.…”
Section: Introductionmentioning
confidence: 99%